1998
DOI: 10.2307/4089506
|View full text |Cite
|
Sign up to set email alerts
|

Nesting Success in Brown-and-Yellow Marshbirds: Effects of Timing, Nest Site, and Brood Parasitism

Abstract: Brown-and-yellow Marshbird (Pseudoleistes virescens) is a nonterritorial blackbird with helpers at the nest that inhabits temperate marshy areas and humid grasslands of Argentina, Uruguay, and Brazil. We estimated nesting success of marshbirds throughout the breeding season (late September to mid-December) and analyzed the effects of brood parasitism and nest-site selection (i.e. nesting substrate) on daily survival rates at different stages of the nesting cycle. Most nests were started in November, and these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 33 publications
5
23
1
4
Order By: Relevance
“…Some authors have reported higher predation rates during the nestling period (reviewed in Martin 1992). However, I found higher predation during the egg stage as reported by others (e.g., Mermoz & Reboreda 1998). Nest predation rates of Grey-headed Bulbul appear to be significantly higher than that of the average rates (71%) recorded for the open cup-nesting tropical birds (Robinson et al 2000;Stutchbury & Morton 2001).…”
Section: Discussioncontrasting
confidence: 42%
“…Some authors have reported higher predation rates during the nestling period (reviewed in Martin 1992). However, I found higher predation during the egg stage as reported by others (e.g., Mermoz & Reboreda 1998). Nest predation rates of Grey-headed Bulbul appear to be significantly higher than that of the average rates (71%) recorded for the open cup-nesting tropical birds (Robinson et al 2000;Stutchbury & Morton 2001).…”
Section: Discussioncontrasting
confidence: 42%
“…Resultado semelhante foi encontrado para a mesma espécie em áreas alteradas, tanto na fase de incubação (59%), como na fase de ninhegos (41%) (Pimentel 1985). A predação tem sido enfatizada como uma importante força seletiva no processo reprodutivo das aves (Mezquida & Marone 2001) sendo o principal fator de perda de ninhos de muitas espécies, em diferentes hábitats e localizações geográficas (Best & Stauffer 1980, Martin 1993, Mermoz & Reboreda 1998, Aguilar et al 1999, 2000, Mezquida & Marone 2002, Picman et al 2002, Lopes & Marini 2005b, Roper 2005, Pinho et al 2006, Duca 2007, Medeiros & Marini 2007. A taxa de predação de ninhos nos trópicos é alta, em torno de 80 a 90%, mas pode variar entre regiões (Ricklefs 1969, Oniki 1979, Stutchbury & Morton 2001, Roper 2003, sendo em geral maior que a encontrada para esta espécie.…”
Section: Causas Da Perdaunclassified
“…MARINI, dados não publicados). A taxa de parasitismo da borda da reserva é considerada baixa em relação a outros locais da região Neotropical onde pode atingir entre 65 e 83% dos ninhos (WOODWORTH 1997, MERMOZ & REBOREDA 1998 Os dados obtidos nesse trabalho permitem concluir que as taxas de predação de ninhos naturais e artificiais, assim como de parasitos de ninho e a abundância relativa de duas espécies de predadores não foram significativamente diferentes entre a borda e interior. Porém não se sabe se essas atuais taxas de predação são normais para a região ou se ainda não houve tempo suficiente de resposta às mudanças dos efeitos de borda na Estação Ecológica de Águas Emendadas.…”
Section: Parasitismo De Ninhosunclassified